2002
DOI: 10.1093/emboj/cdf308
|View full text |Cite
|
Sign up to set email alerts
|

The DnaC helicase loader is a dual ATP/ADP switch protein

Abstract: Helicases are transferred to replication origins by helicase loading factors. The Escherichia coli DnaC and eukaryotic Cdc6/18 helicase loaders contain ATP sites and are both members of the AAA+ family. One might expect that ATP is required for helicase loading; however, this study on DnaC illustrates that ATP is not actually needed for DnaC to load helicase onto single‐strand DNA (ssDNA). In fact, it seems to be a paradox that after transfer of helicase to DNA, DnaC–ATP inhibits helicase action. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(229 citation statements)
references
References 61 publications
12
215
2
Order By: Relevance
“…Like the noncanonical variants of ClpB described in this work, DnaC is not an efficient ATPase, but unlike ClpB, it does not form oligomers. 18 Single-stranded DNA and the helicase DnaB (which is a canonical AAAþ ATPase) stimulate the ATP hydrolysis by DnaC. Moreover, DnaC assembles into oligomers on a scaffold of the hexameric DnaB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like the noncanonical variants of ClpB described in this work, DnaC is not an efficient ATPase, but unlike ClpB, it does not form oligomers. 18 Single-stranded DNA and the helicase DnaB (which is a canonical AAAþ ATPase) stimulate the ATP hydrolysis by DnaC. Moreover, DnaC assembles into oligomers on a scaffold of the hexameric DnaB.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the torsin family, an Asn in the Walker A motif is found in DnaC, a bacterial AAAþ helicase loader. 18 Intriguingly, the biochemical properties of torsinA and DnaC do not fully conform to the AAAþ paradigm: those proteins do not form hexamers and have low ATPase activity in the absence of other macromolecules. 18,19 We hypothesized that the last residue of the Walker A motif may participate in coupling the binding of nucleotides with interactions of an AAAþ ATPase with substrates or partner proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies suggested that ATP bound to DnaC is necessary for DnaC to form an isolable complex with DnaB and to protect DnaC from inactivation by N-ethylmaleimide (Wickner and Hurwitz 1975;Kobori and Kornberg 1982). More recent studies indicate that ATP is not needed for DnaC to interact with DnaB (Davey et al 2002;Galletto et al 2003;Mott et al 2008). Both cryoelectron microscopy of the DnaB -DnaC complex in comparison with DnaB and fluorescence energy transfer experiments indicate that DnaC is bound to the larger (carboxy-terminal) end of the DnaB toroid (Bárcena et al 2001;Galletto et al 2003).…”
Section: Dnaa Is the Replication Initiator In Bacteriamentioning
confidence: 98%
“…Despite the presence in DnaC of motifs shared by AAA þ family members and the high affinity of other AAA þ proteins for ATP, DnaC binds weakly to this nucleotide; the K d is about 8 mM (Davey et al 2002;Galletto et al 2003;Biswas et al 2004). By itself, DnaC is also a feeble ATPase.…”
Section: Dnac Controls the Activity Of Dnabmentioning
confidence: 99%